COMPETITIVE STRENGTHENING THROUGH TRAINING IN DEVELOPMENT OF FINANCIAL ADMINISTRATION AND MARKETING FOR MICRO ENTREPRENEURS IN SIDOARJO REGENCY - Novyandri Taufik Bahtera; Hanifiyah Yuliatul Hijriah; Himmatul Kholidah (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: Strengthening of economic added value in overcoming the problem of poverty in Sidoarjo Regency through the participation of community organizations, one of which is the Muhammadiyah organization through fostering micro-businesses. But apparently there are still problems faced by most members of micro entrepreneurs who are incorporated in the form of inadequate abilities from the aspect of insight and skills. Purpose: This activity aims to increase the capacity of these micro entrepreneurs through a training in the field of financial administration records and product marketing Methods: The method used contains active training, discussion, and practice by organizing workshops and training in financial administration and tax development, and also implementation of practicing online marketing development training with the latest technology such as the use of e-commerce. Results: Micro entrepreneurs have gained insights and abilities in managing business financial administration, taxation for micro entrepreneurs and digital marketing. Conclusion: Partners can improve business competitiveness through increased skills related to the preparation of financial administration, micro business tax literacy and increased marketing through digital marketing.